Problem Based Learning Models on Critical Thinking Ability in Science Lessons of Grade V Elementary School - Adnyani, Ni Putu Sumita; Suniasih, Ni Wayan (Thinking Skills and Creativity Journal, 2023)
21st century learning requires students to have 4C skills, one of which is critical thinking. Critical thinking is a potential that students must train early and must continue to be developed. Therefore, the process of implementing learning in the classroom must be able to train and improve students' critical thinking skills with real problems in science material. This study aims to analyze the effect of Problem Based Learning Model on critical thinking skills in science lessons of grade V elementary school students. This type of research is a pseudo-research with a research design of Nonequivalent Control Group Design. The research sample was grade V elementary school students totaling 61 students. The data collection method used was the test method and the instrument used was an essay test question equipped with an assessment rubric. The analysis technique used descriptive statistical analysis techniques and inferential statistics t-test. The results of data analysis obtained the average critical thinking ability of the experimental group 75.8 and the control group 65.5. Based on the results of the t-test analysis, obtained tcount = 5.65 > ttable = 2.001 at a significance level of 5% with df = 59, then H0 is rejected and Ha is accepted. So, it can be concluded that there is a significant effect of the application of problem-based learning model on critical thinking skills in science lessons of grade V elementary school students.